Cloning and functional verification of Geraniol-10-Hydroxylase gene in Lonicera japonica - Shuping Zhang; Zhenhua Liu; Jia Li; Qian Liu; Yongqing Zhang; Gaobin Pu (PeerJ)
Background Geraniol 10-hydroxylase (G10H) is a cytochrome P450 monooxygenase involved in regulation, which is involved in the biosynthesis of monoterpene. However, G10H is not characterized at the enzymatic mechanism and regulatory function in Lonicera japonica. Methods and Results A gene related to the biosynthesis of monoterpenoid, geraniol 10-hydroxylase, has been cloned from the medicinal plant Lonicera japonica. The gene, LjG10H, encodes a peptide of 498 amino acids with a predicted molecular weight of 54.45 kDa. LjG10H shares a homology of 72.93–83.90% with G10H from other plants. Phylogenetic analysis suggests that the protein encoded by this gene belongs to the cytochrome P450 monooxygenase family. Tissue-specific expression analysis revealed that LjG10H is most highly expressed in flowers. Through heterologous expression in E. coli, the LjG10H protein was purified and its catalytic activity was studied. The results show that the enzyme can catalyze the hydroxylation of geraniol to 10-hydroxygeraniol. Additionally, analysis of Lonicera japonica seedlings with silenced LjG10H revealed a reduction in monoterpenoid content. Conclusions This study demonstrates that LjG10H plays an important role in the biosynthetic pathway of iridoids. This is the first article that ascribes G10H to be associated with the biosynthetic pathway of iridoid. This study provides a theoretical basis for the functional mechanism of LjG10H in regulating iridoid synthesis and provides a valuable resource for molecular breeding studies.